Insidensi Nematoda Gastrointestinal dan Protozoa pada Monyet Ekor Panjang (Macaca fascicularis) Liar di Taman Wisata Alam (TWA) Pulau Weh Sabang - Rahmi, Erdiansyah; Hanafiah, Muhammad; Sutriana, Amalia; Hambal, Muhammad; Wajidi, Farid (Fakultas Peternakan Universitas Jambi, 2010)
The research aims to find out the incidence of gastrointestinal parasite in wild long tail macaque in wildlife reserve park, Weh Island, Sabang. For that purpose, fecal specimens from 25 wild long tail macaques in Weh Island- Sabang were collected. The fresh faeces samples were then preserved using AFA (alcohol-formal-acetic) liquid prior to be examined in Parasitology Laboratorium, Faculty of Veterinary Medicine, Syiah Kuala University. The presence of gastrointestinal parasite was observed using centrifuge method as well as Boray sedimentation method. The obtained data were tabulated and analyzed descriptively. The result revealed that two parasite species were found in gastrointestine; Eimeria spp. (12%) and Strongloides spp. (8%). It could be concluded that the prevalence of gastrointestinal parasite in wild long tail macaque in wildlife reserve park, Weh Island- Sabang was considered mild.